2015
DOI: 10.1097/mpg.0b013e3182496b35
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole for the Treatment of GERD in Infants Ages 1–11 Months

Abstract: The discontinuation rate owing to symptom worsening did not differ significantly between infants receiving esomeprazole versus those receiving placebo. Improved diagnostic criteria in this age group are needed to identify infants with GERD who may benefit from acid suppression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 22 publications
2
41
0
8
Order By: Relevance
“…The review focused on 12 randomized, controlled and crossover studies in children ranging in age from 0–17 years. In addition to the systematic review, we included in our review a multicenter, randomized, double‐blind, placebo‐controlled trial published in 2012 that compared the efficacy and safety of esomeprazole in infants to provide more updated information . Table provides a summary of these trials …”
Section: Efficacy Of Proton Pump Inhibitors In Infants Children Andmentioning
confidence: 99%
“…The review focused on 12 randomized, controlled and crossover studies in children ranging in age from 0–17 years. In addition to the systematic review, we included in our review a multicenter, randomized, double‐blind, placebo‐controlled trial published in 2012 that compared the efficacy and safety of esomeprazole in infants to provide more updated information . Table provides a summary of these trials …”
Section: Efficacy Of Proton Pump Inhibitors In Infants Children Andmentioning
confidence: 99%
“…These observations suggest that pathological GER is an unlikely cause of infant irritability under the age of 3 months [40]. Several placebocontrolled prospective trials with PPIs in infants presenting with "excessive crying and reflux-like symptoms" have been performed and show negative results, with an increased incidence of adverse events in the PPI group sometimes as being the only difference in outcome [56][57][58].…”
Section: H²-receptor Antagonists and Proton Pump Inhibitorsmentioning
confidence: 90%
“…GERD may cause excessive crying in infants [40]. The concept that infant irritability and sleep disturbances are manifestations of GER is largely extrapolated from adult descriptions of heartburn and sleep disturbances that improve with antacid therapy OA [158] 1-11 month During double-blind treatment, there were no significant differences between pantoprazole and placebo in withdrawal rates due to lack of efficacy Winter (2012) OA [56] 1-11 month During double-blind treatment, there were no significant differences between esomeprazole and placebo in withdrawal rates due to lack of efficacy OA [159] 1-11 years Symptom improvement Gold (2007) OA [160] 12-17 years Symptom improvement Shashidhar (2013) Rev [161] 0-18 years PPIs are effective in healing reflux esophagitis in children of all ages but do not improve GER-related symptoms in infants The table is not exhaustive but lists the papers on Pubmed between 2007 and 2013 with "proton pump inhibitor infant" and "proton pump inhibitor pediatric" as search terms and illustrates the differences in outcome according to age of the patients PPI proton pump inhibitor, H²RA histamine receptor antagonists, RCTs randomized controlled trials, GERD gastroesophageal reflux disease [1]. However, there is no evidence for this hypothesis.…”
Section: H²-receptor Antagonists and Proton Pump Inhibitorsmentioning
confidence: 95%
“…Notably, Moore et al[24] enrolled infants with endoscopically confirmed GORD and found omeprazole significantly reduced the reflux index (percentage of total duration pH < 4) in these infants compared with placebo, but irritability improved regardless of treatment. In the most recent randomised controlled trial of PPI (Esomeprazole) for the treatment of symptomatic GORD, without endoscopy, all children were initially treated with PPI and then randomised to continuation of PPI or placebo[25]. It found no statistically significant difference in apparent treatment failure between the PPI or placebo group.…”
Section: Action and Efficacy Of Ppimentioning
confidence: 99%